Pengaruh Budaya Organisasi, Gaya Kepemimpinan, dan Work Life Balance terhadap Employee Engagement Pegawai Generasi Y dan Z dalam Meningkatkan Kinerja di Bank XYZ - Saryo; Harun, Paulina (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
This study examines the impact of organizational culture, leadership style, and work-life balance on employee performance at Bank XYZ, with employee engagement as a mediator. The sample consists of 125 permanent employees from Generation Y and Z working at the head office in Jakarta and regional offices. An online questionnaire was used to collect primary data, and Structural Equation Modeling (SEM) with Partial Least Squares (SEM-PLS) was employed for analysis. The results indicate that organizational culture, leadership style, and work-life balance significantly influence employee engagement and performance. This study provides insights into the factors that drive employee performance in the banking sector, particularly among younger generations. The findings have implications for Bank XYZ's human resource management strategies, highlighting the importance of fostering a positive organizational culture, effective leadership, and work-life balance to enhance employee engagement and performance.